Model Kolaboratif Dinas Kebudayaan, Pemuda dan Olahraga dan Pariwisata Dengan Asosiasi Pengelola Wisata Tirta Kabupaten Klaten Dalam Meningkatkan Kunjungan Wisatawan Pasca Pandemi - Maulana, Syaiful (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The increase in tourist visits post-pandemic at water tourism destinations in Klaten Regency has led to cross-sector collaboration between the Association of Water Tourism Managers and the Department of Culture, Youth, and Sports, and Tourism. This research aims to uncover the collaborative communication model between the association and the department post-pandemic. Employing a qualitative approach with a phenomenological methodology, the study is conducted across all water tourism sites affiliated with the association. Data collection involves interviews with government officials and tourism managers, along with on-site observations and the analysis of existing documents. The collaboration has evolved in response to the initial conditions presented by the COVID-19 pandemic. The collaborative process encompasses dialogue, trust-building, commitment to the process, and shared understanding. The outcomes of this cross-sector collaboration include training initiatives geared towards supporting the increase in tourist visits. This research sheds light on how the collaboration unfolds under the backdrop of the initial condition, namely the COVID-19 pandemic. The collaborative process involves a series of steps, from dialogue to building trust, commitment to the collaborative process, and sharing understanding. The ultimate result of this cross-sector collaboration is the implementation of training programs aimed at bolstering the influx of tourists.